(untitled) (Experimental biology, 2015)
In first time was leaded analysis of a lot of species of gastropoda mollusks in the region of the river Shu. The ecological particularity of dissemination, reproduction and evolution of freswater mollusks of the region of the river Shu. In was investigated of morphology of laying of egges of a lot of species of the mollusks. On basis of analysis of dynamic of dimensional and age structure of population of species in the vegatative period was determined of deadline the lifes cycle for 5 species of the mollusks.